Formation of doughnut and super-Gaussian intensity distributions of laser radiation in the far field using a bimorph mirror. (January 2018) - Lylova, A.N.; Sheldakova, Yu.V.; Kudryashov, A.V.; Samarkin, V.V.
Abstract: We consider the methods for modelling doughnut and super-Gaussian intensity distributions in the far field by means of deformable bimorph mirrors. A method for the rapid formation of a specified intensity distribution using a Shack – Hartmann sensor is proposed, and the results of the modelling of doughnut and super-Gaussian intensity distributions are presented.